Update of Cestodes Parasitizing Neotropical Hystricomorphic Rodent - Jones, Kegan Romelle (Frontiers in Veterinary Science, 2022)
This review aims at identifying cestodes that are present in hunted rodent species in the neo-tropical region. The rodent species that was investigated were the capybara (Hydrochoerus hydrochaeris, Linnaeus, 1766), lappe (Cuniculus paca, Linnaeus, 1766), agouti (Dasyprocta leporina, Linnaeus, 1758), chinchilla (Chinchilla chinchilla, Lichtenstein, 1829), Trinidad spiny rat (Proehimys trinitatus, Allen and Chapman, 1893), nutria (Myocastor coypus, Molina, 1782) and vizcacha (Lagostomus maximus, Desmarest, 1817). These rodent species are utilized for their meats in many rural communities in the Caribbean and South America. These rodents belong to the hystricomorphic group. Raillietina demerariensis Daniels, 1895 was commonly found in the gastrointestinal tract of D. leporina, C. paca and P. trinitatus. Similarly, in the liver, muscle and subcutaneous tissue the metacestodes on Echinococcus vogeli Daniels, 1895 and Echinococcus oligarthrus was found in the lappe and agouti. The capybara was found to have the most species of cestodes in its gastrointestinal tract when compared to the agouti and lappe. However, metacestodes were not recorded in the tissues of the capybara. This surprising feature shows the effect of the difference in feeding habits between the capybara and the agouti and lappe. The literature reviewed in this study includes scientific publications on cestodes and metacestodes of Hystricomorphic rodents. An exhaustive search was performed using the digital repositories in Google Scholar, Scielo, Redalyc, Scopus and Pubmed. Literature searched spanned the years 1970 to 2021. Cestodes of zoonotic significance were E. vogeli and E. oligarthrus, with humans becoming infected when consuming eggs of contaminated food and water.